1989
DOI: 10.1007/bf01658401
|View full text |Cite
|
Sign up to set email alerts
|

Renal autotransplantation

Abstract: In the period, 1973-1985, a total of 305 renal autotransplantations (often with extracorporeal repair) were performed in 274 patients for fibromuscular (56) or atherosclerotic (98) renovascular disease, nephrolithiasis (97), renal tumor (15), or ureteral injury (8). One-third of the patients had reduced renal function, and approximately half of the patients with renovascular lesions presented with severe or malignant hypertension. The postoperative mortality rate of 4% was related to age over 60 years and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 8 publications
0
17
0
2
Order By: Relevance
“…Flatmark et al. [27] reported a mortality rate of 4% of 274 autotransplanted patients and 3.6% of the kidneys were lost. In these cases the indications for operation were renovascular diseases in 56% and nephrolithiasis in 35%.…”
Section: Discussionmentioning
confidence: 99%
“…Flatmark et al. [27] reported a mortality rate of 4% of 274 autotransplanted patients and 3.6% of the kidneys were lost. In these cases the indications for operation were renovascular diseases in 56% and nephrolithiasis in 35%.…”
Section: Discussionmentioning
confidence: 99%
“…7 More recent studies have demonstrated the safety and applicability of renal autotransplant in selected cases. Sevmis and coworkers have demonstrated improvements in creatinine concentration, creatinine clearance, and blood pressure in 5 patients with renovascular hypertension.…”
Section: Renovascular Diseasementioning
confidence: 99%
“…In their series of 305 renal autotransplants, Flatmark and associates performed 15 autotransplants due to renal tumors. 7 All 15 patients had 1 functioning kidney before autotransplant. Frozen sections were performed intraoperatively to ensure that tumor-free margins were achieved.…”
Section: Neoplastic Diseasementioning
confidence: 99%
“…Das Risiko postoperativer Transplantatkomplikationen ist gering und die Transplantatverlustrate liegt um 4% [7,11].…”
Section: Autotransplantationunclassified